(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the specifics of teaching a foreign language, the main aim of which is to develop communicative competence of the learners. It also emphasises the need for a humanistic approach to learning, which creates positive conditions for the active development of personality.